Risk of second primary cancers in multiple myeloma survivors in German and Swedish cancer registries - Chen, Tianhui; Fallah, Mahdi; Brenner, Hermann; Jansen, Lina; Mai, Elias K.; Castro, Felipe A.; Hemminki, Kari (Scientific reports, 2016)
We aimed at investigating the distribution and risk of second primary cancers (SPCs) in multiple myeloma (MM) survivors in Germany and Sweden to provide etiological understanding of SPCs and insight into their incidence rates and recording practices. MM patients diagnosed in 1997-2010 at age ≥15 years were selected from the Swedish (nationwide) and 12 German cancer registries. Standardized incidence ratios (SIRs) were used to assess risk of a specific SPC compared to risk of the same first cancer in the corresponding background population. Among 18,735 survivors of first MM in Germany and 7,560 in Sweden, overall 752 and 349 SPCs were recorded, respectively. Significantly elevated SIRs of specific SPCs were observed for acute myeloid leukemia (AML; SIR = 4.9) in Germany and for kidney cancer (2.3), AML (2.3) and nervous system cancer (1.9) in Sweden. Elevated risk for AML was more pronounced in the earlier diagnosis period compared to the later, i.e., 9.7 (4.2-19) for 1997-2003 period versus 3.5 (1.5-6.9) for 2004-2010 in Germany; 3.8 (1.4-8.3) for 1997-2003 versus 2.2 (0.3-7.8) for 2004-2010 in Sweden. We found elevated risk for AML for overall, early diagnosis periods and longer follow-up times in both populations, suggesting possible side effects of treatment for MM patients.